Assessment of pharmacokinetics, bioavailability and protein binding of anacetrapib in rats by a simple high‐performance liquid chromatography–tandem mass spectrometry method. (8th August 2016) - Kim, Sang‐Bum; Kim, Ki Taek; Joo, Jeongmin; Seo, Kyung‐Ah; Hwang, Hayoung; Kim, Soong‐Hyun; Song, Minsoo; Lee, Sungwoo; Jahn, Alexander; Cho, Hyun‐Jong; Kim, Dae‐Duk; Yoon, In‐Soo
Abstract: Anacetrapib is a potent and selective CETP inhibitor and is undergoing phase III clinical trials for the treatment of dyslipidemia. A simple and sensitive high‐performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) method for the quantification of anacetrapib in rat plasma was developed and validated using an easily purchasable compound, chlorpropamide, as an internal standard (IS). A minimal volume of rat plasma sample (20 μL) was prepared by a single‐step deproteinization procedure with 80 μL of acetonitrile. Chromatographic separation was performed using Kinetex C18 column with a gradient mobile phase consisting of water and acetonitrile containing 0.1% formic acid at a flow rate of 0.3 mL/min. Mass spectrometric detection was performed using selected reaction monitoring modes at the mass/charge transitions m/z 638 → 283 for anacetrapib and m/z 277 → 175 for IS. The assay was validated to demonstrate the selectivity, linearity, precision, accuracy, recovery, matrix effect and stability. The lower limit of quantification was 5 ng/mL. This LC‐MS/MS assay was successfully applied in the rat plasma protein binding and pharmacokinetic studies of anacetrapib. The fraction of unbound anacetrapib was determined to be low (ranging from 5.66 to 12.3%), and the absolute oral bioavailability of anacetrapib was 32.7%.